Experimental investigation on effect of surfactant on cooling dynamics of stainless steel. (2021) - Kumar, M. Manoj; Inbaoli, A.; Kumar, C.S. Sujith; Vineesh, K.P.
Abstract: Heat removal from a hot body is of vital importance for many industries like chemical, nuclear, and production industries. Cooling occurs in three stages: film boiling, nucleate boiling, and convective boiling. This study investigates the effect of surfactant on these three distinct stages of heat transfer with stainless steel (304). Contact angles are measured for deionized water and surfactant solutions (sodium dodecyl sulphate) and the critical micellar concentration of surfactant was determined. Vertical quenching tests were carried out in deionized water with and without the addition of surfactant under atmospheric pressure and temperature. The stainless-steel sample was heated to 480°C and then immersed into liquid tank. Type K thermocouple was used for measuring the centre temperature and cooling dynamics of the stainless-steel sample were studied. Added surfactant exhibits significant influence on the cooling behaviour. However, influence of surfactant largely governed by prevailing boiling regimes. In film boiling regime, deposition of surfactant stabilises the vapour layer, which prolonged the film boiling time. In nucleate boiling, surfactant facilitates enhanced cooling especially at the later stage of bubble incipience. Additionally, the temperature gradient in the film boiling is much lower than that of deionized water. A finite element model has been developed for determining the heat transfer coefficient.